The Level of Oxidative Stress Markers in Generalised Periodontitis in the Setting of Bronchiectasis - Anatoly P. Kibkalo; Artem K. Sarkisov; Ekaterina A. Polunina; Karen A. Sarkisov (Кубанский научный медицинский вестник, 2019)
Aim. To analyse the level of oxidative stress markers and the value of dental indices characterising the state of periodontal tissue in patients with generalised periodontitis (GP) both without somatic pathology and with bronchiectasis.Materials and methods. Over the period from 2015 to 2017, a total of 90 GP patients were examined, including 40 patients without somatic pathology and 50 patients with bronchiectasis. The control group consisted of somatically healthy individuals with intact periodontium (n=40). The following indices were calculated for all examined individuals: PMA, PI, Muhlemann and OHI-s. The level of oxidative stress markers in oral fl uid was determined: total superoxide dismutase (SOD) of all three types (Cu/Zn-SOD + Mn-SOD + Fe-SOD), products of advanced protein oxidation and malondialdehyde.Results. The study established the intensifi cation of oxidative stress in GP patients without somatic pathology and with bronchiectasis. Patients with comorbid pathologies demonstrated a greater severity of oxidative stress. The analysis revealed a significant correlation between the values of dental indices (PMA, PI, Muhlemann, OHI-s) and the level of oxidative stress markers both in GP patients without somatic pathology and with bronchiectasis. Furthermore, this correlation is stronger in patients with comorbid pathologies.Conclusion. The presence of comorbid pulmonary pathologies in the form of bronchiectasis in patients with generalised periodontitis can act as an aggravating factor in the development of periodontal lesions.